Diagnostic accuracy of preoperative ultrasonography-guided fine-needle aspiration biopsy in distinguishing malignancy in large thyroid nodules: A systematic review, meta-analysis, and meta-regression - Zulfa, Putri O.; Iqhrammullah, Muhammad; Zufry, Hendra (Narra J, 2025)
Controversy persists regarding the effectiveness of ultrasonography-guided fine-needle aspiration biopsy (US-FNAB) in distinguishing malignancies in large thyroid nodules. The prevailing belief that larger thyroid nodules inherently pose a higher risk of malignancy has led to a common practice of suggesting thyroidectomy for large thyroid nodules. Herein, the aim of this study was to assess the diagnostic accuracy of preoperative US-FNAB for distinguishing malignancy in large thyroid nodules. A search for published records was carried out on 20 October 2023, utilizing the search feature available on PubMed, Scopus, Embase, and Google Scholar. Patients with large thyroid nodules (3 cm or larger) who underwent preoperative US-FNAB and postoperative histopathological tests were included. Related outcomes, including false positive (FP), false negative (FN), true negative (TN), true positive (TP), specificity, and sensitivity, were extracted from each study. Pooled specificity and sensitivity were estimated, and the summarized receiver operating characteristic (sROC) curve, along with the summarized area under the curve (sAUC), was calculated. Out of 133 articles identified across four databases, 10 studies with a total sample of 2752 patients were included. The overall diagnostic sensitivity was 72% (95%CI: 50–86%; p=0.00) and specificity was 96% (95%CI: 87–90%; p=0.00). The positive predictive value (PPV) and negative predictive value (NPV) were 93% (95%CI: 89–98%) and 75% (95%CI: 72–79%), respectively. sAUC was 93%, suggesting the diagnostic tool is accurate. Meta-regression analysis revealed that factors such as the number of samples, country (high-income vs upper-middle income), demographic characteristics (age and gender), and different thyroid size cut-off values did not significantly impact the sensitivity or specificity of US-FNAB. In conclusion, the present study confirms the reliability of US-FNAB in distinguishing malignancy in large thyroid nodules, emphasizing its role in reducing unnecessary thyroidectomy by identifying high-risk patients and challenging the conventional practice of routine thyroidectomy for large thyroid nodules.